RESPON PERTUMBUHAN STEK BATANG BUNGA MAWAR MERAH (Rosa damascena P.Mill.) TERHADAP KONSENTRASI DAN LAMA WAKTU PERENDAMAN AIR KELAPA MUDA - Helena Murni; Putu Eka Pasmidi Ariati; Cokorda Javandira; I G.N. Alit Wiswasta; I Ketut Widnyana (Agrofarm: Jurnal Agroteknologi, 2023)
This study entitled "Response of growth of stem cuttings of red roses (Rosa damascena P.Mill.) to concentrations and immersion time of young coconut water in Batu Bulan Village, Banjar Sasih, Sukawati District, Gianyar Regency". The implementation started from January 10 2021 to April 23 2021. The research aims to determine the concentration and duration of soaking young coconut water which is good for the growth of red rose plants (Rosa damascena P.Mill), flower plants are propagated generatively and vegetatively. The method used in this study was stem cuttings, namely by cutting selected parts of the plant stems. Coconut water also contains auxin and cytokinins which play a role in encouraging cells to divide and elongate rapidly so as to increase growth rate. This study used a randomized block design (RBD). .with 9 repetitions and 3 repetitions there were 48 polybags. The treatments were 0% K0L0, 25% K1L1, 50% K2L2, 75% K3L3, and 100% K4L4. The results showed that the long time immersion of young coconut water (K4L3) resulted in the number of times the first leaves appeared (K4L4) 43.75 (strands), branch length (K3L4) 45.50 (cm) number of primary leaves, (K3L4) 45.50 (strands), length of primary leaves (K4L2) 8.25 (cm) stem diameter (K3L4) 4.07.(cm) .